Perceived Impact of Quarantine on Loneliness, Death Obsession, and Preoccupation With God: Predictors of Increased Fear of COVID-19 - Enea, Violeta; Eisenbeck, Nikolett; Petrescu, Teodora Carina; Carreno, David F. (Frontiers in Psychology, 2021)
Most countries are facing the societal challenging need for a new quarantine period due to the increasing number of COVID-19 infections, indicating a second or even third wave of disease. The COVID-19 pandemic has brought to the surface existential issues that are typically less present in people’s focal attention. The first aim of this study was to identify some of these existential struggles such as increased feelings of loneliness, death obsession, and preoccupation with God. Secondly, we explored the association of these factors with the increased fear of coronavirus during the quarantine. Data was collected from 1340 Romanian adults using a cross-sectional web-based survey design in the midst of the national lockdown period of COVID-19. Participants completed measures of COVID-19 related loneliness, death obsession, and preoccupation with God twice; first, thinking about the period before the pandemic, and second, for the current situation, during the quarantine. Then, they completed a fear of COVID-19 measure. Participants perceived an increase in the feelings of loneliness, death obsession, and preoccupation with God during the confinement. Furthermore, gender, knowing someone diagnosed with COVID-19, loneliness, death obsession and preoccupation with God predicted fear of COVID-19. Interestingly, days in isolation did not predict fear of COVID-19 nor were associated with feelings of loneliness. In line with existential positive psychology, these results highlight the importance of policies and interventions targeting the experience of loneliness, spiritual beliefs, and particularly those aimed to promote death acceptance, in order to alleviate intense fear of COVID-19.